A novel KCNA5 Mutation Implicates Tyrosine Kinase Signaling in Human Atrial Fibrillation - Yang, Tao (2010)
BACKGROUND: Emerging evidence has strongly implicated hereditary determinants for atrial fibrillation (AF). Loss-of-function mutations in KCNA5 encoding the ultra-rapid delayed rectifier potassium current (I(Kur)) have been identified in AF families. OBJECTIVE: Our study sought to present the clinical and biophysical phenotypes in a KCNQ5 mutation with deletion of 11 amino acids in the N-terminus of the protein, which was identified in patients with lone AF. METHODS: Patients with AF, confirmed by ECG, were prospectively enrolled in the Vanderbilt AF Registry, which comprises clinical and genetic databases. A KCNQ5 mutation was generated by mutagenesis for the electrophysiology characterization. RESULTS: We identified a novel 33-bp coding region deletion in 2 Caucasian probands. One proband was part of a kindred that included 4 other members with AF, and all were mutation carriers. The mutation results in deletion of 11 amino acids in the N-terminus of the protein, a proline-rich region as a binding site for Src homology 3 (SH3) domains associated with Src-family protein tyrosine kinase (TK) pathway. In transfected cells, the mutant caused ~60% decreased I(Kur) vs wild-type (WT) (75±8 vs 180±15 pA/pF, P<0.01) and dominant-negative effect on WT current (105±10 pA/pF, P<0.01). Pretreatment with the Src inhibitor PP2 prevented v-Src TK from 90% suppressed WT current. By contrast, the mutant channel displayed no response to v-Src TK. CONCLUSIONS: Our data implicate abnormal atrial repolarization control due to variable TK signaling as a mechanism in familial AF, and thereby suggest a role for modulation of this pathway in AF and its treatment.